2010
DOI: 10.1002/jbt.20318
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A induction of sulfotransferases in rats

Abstract: Biochanin A (BCA) is a dietary isoflavone present in red clover (Trifoliumn pretense) and many herbal products. BCA has been reported to have chemopreventive actions against various cancers including prostate, breast, colon cancer, and so on. Sulfotransferases are a family of phase II drug-metabolizing enzymes, which are important for xenobiotic detoxification and regulation of biological signaling molecule biological activities. Sulfotransferase gene expressions are regulated by different hormones and xenobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…[4][5][6] Furthermore, previous studies have reported that it has antimicrobial and anticancer activities. [7][8][9] These properties, in addition to the fact that BCA inhibits phase I and induces phase II metabolizing enzymes, 10) encouraged us to investigate its effectiveness in preventing acute liver injury in rats.…”
mentioning
confidence: 99%
“…[4][5][6] Furthermore, previous studies have reported that it has antimicrobial and anticancer activities. [7][8][9] These properties, in addition to the fact that BCA inhibits phase I and induces phase II metabolizing enzymes, 10) encouraged us to investigate its effectiveness in preventing acute liver injury in rats.…”
mentioning
confidence: 99%
“…Biochanin A can significantly induce sulfotransferases enzyme activities and gene expressions in rat liver and intestines. These results may also provide information on the anticancer activities of Biochanin A (Chen et al, 2010).…”
Section: Chemo Preventive Propertiesmentioning
confidence: 98%
“…AdpaMn was synthesized as reported [8], Hepes(4-(2-Hydroxyethyl)-1-piperazineethanesulfonic acid) buffer (50 mM Hepes, 100 mM NaCl, 5 mM Na 2 CO 3 , pH 7.4) was prepared with double-distilled water. Both apoTf and compounds were dissolved in Hepes buffer.…”
Section: Generalmentioning
confidence: 99%
“…Recently, we found that Mn(II) compounds with N-substituted di(picolyl)amine inhibits the proliferation of human glioma cells (U251) and HepG-2 cells in vitro. Moreover, Mn(II) compounds [(Adpa)Mn(Cl)(H 2 O)] (Adpa = bis(2-pyridylmethyl)amino-2-propionic acid) (AdpaMn) (Scheme 1) can target mitochondria and inhibits the proliferation of U251 with low IC 50 (9.5 lM) in vitro [7,8]. A significant challenge for biomedical use is the safety of metal compounds, because non-specific interactions between compounds and human plasma proteins can 1386-1425/$ -see front matter Ó 2012 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%